1997
DOI: 10.1152/ajpheart.1997.272.5.h2115
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac inotropic actions of urocortin in conscious sheep

Abstract: Urocortin (Ucn) is a recently isolated peptide related to the corticotropin-releasing factor (CRF) family, which can produce hemodynamic and hormonal actions in conscious rats. This study examined in detail the cardiovascular actions of Ucn and CRF after intravenous injection in chronically instrumented, conscious sheep. Injection of Ucn produced dose-dependent changes in cardiac contractility [rate of increase of aortic flow (dF/dt)], maximum aortic flow (Fmax), mean arterial pressure (MAP), heart rate (HR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
96
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 0 publications
10
96
0
4
Order By: Relevance
“…3 These studies suggest that UCN, unlike CT-1, is a cardioprotective agent that does not induce a hypertrophic response. Moreover, although 100 g of UCN administered to sheep produced changes in cardiac function (18), no hemodynamic changes were observed in response to the lower doses of UCN used in the isolated rat hearts used in these experiments. A previous study on rats revealed that a subcutaneous injection of UCN caused a significant decrease in mean arterial blood pressure; hence, it acts as a hypotensive agent (59).…”
Section: Table II Assessment Of Percent Cell Death Annexin V-positivmentioning
confidence: 76%
See 1 more Smart Citation
“…3 These studies suggest that UCN, unlike CT-1, is a cardioprotective agent that does not induce a hypertrophic response. Moreover, although 100 g of UCN administered to sheep produced changes in cardiac function (18), no hemodynamic changes were observed in response to the lower doses of UCN used in the isolated rat hearts used in these experiments. A previous study on rats revealed that a subcutaneous injection of UCN caused a significant decrease in mean arterial blood pressure; hence, it acts as a hypotensive agent (59).…”
Section: Table II Assessment Of Percent Cell Death Annexin V-positivmentioning
confidence: 76%
“…Indeed UCN, but not CRF, induces a dose-dependent increase in heart rate, cardiac output, and coronary blood flow (18). Moreover, cardiac CRF-R2␤ expression is modulated by endotoxin, a potent inducer of cardiovascular dysregulation, further suggesting a possible link between UCN and the cardiovascular response to stress (19).…”
Section: Urocortin (Ucn)mentioning
confidence: 95%
“…Although both receptors are found in the central nervous system, CRFR2 is particularly abundant in the periphery, including the heart and systemic vasculature (6-10). UcnII and -III bind selectively to CRFR2, with no appreciable activity at CRFR1 (3, 5).CRF and UcnI both demonstrate vasodilatory, inotropic, and chronotropic effects on the cardiovascular system via activation of CRFR2 on cardiac myocytes and in the systemic vasculature (2,(11)(12)(13)(14). These actions are absent in CRFR2-deficient mice (15, 16).…”
mentioning
confidence: 99%
“…CRF and UcnI both demonstrate vasodilatory, inotropic, and chronotropic effects on the cardiovascular system via activation of CRFR2 on cardiac myocytes and in the systemic vasculature (2,(11)(12)(13)(14). These actions are absent in CRFR2-deficient mice (15,16).…”
mentioning
confidence: 99%
“…These effects of urocortins can be summarized as follows; a dose-dependent increase in heart rate, cardiac output, coronary blood flow (8), coronary vasodilatation and positive inotropic effect (9), protection against ischemic and reperfusion injury in ventricular myocytes, a diminution in free radical damage following myocardial infarction (10,11), stimulation of cardiac natriuretic peptide secretion, decrease in left atrial pressure and peripheral vascular resistance (12), decrease in blood pressure, reduction of serum catecholamine levels in hyperadrenergic hypertension (13).…”
Section: Introductionmentioning
confidence: 99%